Increased association of the ERG oncoprotein expression in advanced stages of prostate cancer in Filipinos. Issue 11 (9th June 2014) - Raymundo, Eliza M.; Diwa, Michele H.; Lapitan, Marie Carmela M.; Plaza, Aladin B.; Sevilleja, Jesus Emmanuel; Srivastava, Shiv; Sesterhenn, Isabell A.
<x xml:space="preserve">Abstract</x> BACKGROUND Filipinos with prostate cancer (CaP) are at increased risk of harboring advanced stages and lower survival rates compared to other Asians. This study aims to investigate prevalence of ETS‐related gene (ERG) oncoprotein overexpression in Filipinos as surrogate of TMPRSS2‐ERG gene fusions, using a highly specific monoclonal antibody (ERG‐MAb), and conduct the first attempt to study the role of genetic alterations in the aggressive tumor biologic behaviour of CaP among Filipinos. METHODS This case‐matched, case‐control retrospective study evaluated ERG expression in Filipino patients diagnosed with CaP and its effect on stage and Gleason grade of their disease. Men who underwent radical prostatectomy for organ‐confined disease at the University of the Philippines‐Philippine General Hospital (UP‐PGH) comprised the organ‐confined cohort. Age‐matched adults who had trans‐rectal ultrasound‐guided prostate (TRUSP) biopsy or trans‐urethral resection of the prostate (TURP) with bilateral orchiectomy for T4 or stage IV CaP composed the advanced disease cohort. RESULTS Overall ERG expression frequency of 23.08% (N = 104) was demonstrated, with a higher rate observed in the advanced disease cohort (32.69%) compared to the organ‐confined group (13.46%). Furthermore, ERG overexpression was only detected among intermediate and high‐risk tumors. A high‐specificity (98.08%) of the ERG‐MAb for malignant prostatic cells was likewise demonstrated. CONCLUSIONS In contrast to higher ERG frequency in Western countries, it is much lower in Filipino CaP, which is similar to lower rates noted from other Asian countries. The 98.08% specificity of ERG oncoprotein for prostate tumor cells combined with its increased association in advanced disease, suggests for prognostic potential of ERG that may aid clinicians in treatment decisions for Filipino CaP patients. Prostate 74:1079–1085, 2014. © 2014 Wiley Periodicals, Inc.